Behavioural responses to co‐occurring threats of predation and ultraviolet radiation in Daphnia. (22nd April 2020) - Ekvall, Mikael T.; Sha, Yongcui; Palmér, Tobias; Bianco, Giuseppe; Bäckman, Johan; Åström, Kalle; Hansson, Lars‐Anders
Abstract: Organisms in the wild are faced with multiple threats and a common response is a change in behaviour. To disentangle responses to several threats, we exposed two differently sized species of the freshwater invertebrate Daphnia to solar ultraviolet radiation (UVR) and predation from either moving pelagic or benthic ambush predators. Using an advanced nanotechnology‐based method, we tracked the three‐dimensional movements of those mm‐sized animals at the individual level. Each behavioural trial was performed both under conditions resembling night (no UVR) and day (UVR) and we examined patterns of the depth distribution and swimming speed by Daphnia across three treatments: no predator (control); bottom‐dwelling damselfly ( Calopteryx sp.); and fish (stickleback, Pungitius pungitius ) predators. We also quantified the actual predation rate by the two predators on the two Daphnia species, Daphnia manga and Daphnia pulex . We show that individual Daphnia are able to identify predators with different feeding habitats, rank multiple and simultaneously occurring risks and respond in accordance with the actual threat; complex responses that are generally associated with larger animals. In a broader context, our results highlight and quantify how a cocktail of everyday threats is perceived and handled by invertebrates, which advances our understanding of species distribution in space and time, and thereby of population dynamics and ecosystem function in natural ecosystems.